Tiger Grass Industry in Marigondon Norte, San Andres, Romblon: Implications for Research and Development - Sespene, Jeter; Fetalvero, Eddie; Faminial, Tomas (Romblon State University Research Journal, 2011)
This study established a comprehensive baseline data among 100 tiger grass farmers in the area in Marigondon Norte, San Andres, Romblon. Farmers’ demographic and socio-economic profiles were determined. Farm-related variables such as farm profiles, farm inputs, farm outputs, farming practices and marketing practices were also described. It was found out that if the farming and marketing practices of the farmers were to be improved, the industry can be a promising economic activity in the village. Findings further support the advocacy that tiger grass could be a potential commodity for agri-business in the uplands. RSU and other agencies can utilize the findings of this study as benchmark in initiating R&D program for tiger grass.